Maunath Bhanjan City: An Appraisal of Urban Land Use, Change and Characteristics - Bharati, Sanajay Kumar; Sharma, P. R. (National Geographical Journal of India, 2022)
Land use refers to the physical and functional structure of land occupancy of towns and cities. It involves the study of layout pattern of internal structure, street pattern, alignment and architecture of buildings, densities and the different functions of the city. Cities are always developed and transformed through the interaction between the different socio-cultural, political, economic, and technological forces. Hence, these forces create the urban land use and its pattern in the city. Urban geography is studied with three dimensions- urban histogenesis and evolution, urban land use and morphology, and urban planning (Sharma, et al. 2005). This paper aims to analyse land use, its change and characteristics of Maunath Bhanjan city (Uttar Pradesh). The city is significant for cotton textile and handicrafts as well as other industrial units in the recent past. Due to well connected transport network and an urban service centre, it has influenced the spatial expansion as residential, commercial, industrial and public, semi-public, infrastructure, recreational and other land use of the city. Finally, an analysis of urban land use has been explored from map of 2002 and intensive field survey was carried out primarily on the basis by mosaiced Google Earth Satellite Imageries of 2013 for demarcation of existing urban land uses.